Post-Power Syndrome dan Perubahan Perilaku Sosial Pensiunan Guru - Abdul Rahmat (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2016)
This study intended to determine the symptoms and the factors of post-power syndrome, as well as some efforts of the teachers in deal with retirement. The qualitative method was used in this study and data was collected through observation, interview and some documentations studied. Sources of data were two retired teachers in MAN 2 Yogyakarta. The result shown some symptoms experienced by the subjects comprised to get closer in worship activities, but emotionally be more temperamental. The most prominent factors of post-power syndrome among the two informants included the loss of social contact with their co-workers, in addition to losing positions, loss of dignity and a sense of meaning, as well as the loss of income sources. Due to retirement, their activities and routines seemed disconnected from other teacher’s activities so both of them felt losing social contact with colleagues. Some efforts for minimizing the symptoms of post-power syndrome was involving in forum gathering that held by the school.